Labor Market Flows and Equilibrium Search Unemployment - Pietro Garibaldi; Etienne Wasmer (Institute for the Study of Labor (IZA), 2001)
This paper explicitly differentiates between unemployment and inactivity, by defining inactivity as a state in which individuals do not search for jobs when non-employed. Facing changes in the value of inactivity, individuals transit through three labor market states. In steady-state, we hence have a theory of equilibrium unemployment determined by both matching frictions and labor market participation margins. The paper firstly rationalizes and quantitatively accounts for the existence of large flows between employment, unemployment and inactivity. Secondly, it shows that unemployment and aggregate wages rise because some of the employed workers are unattached to the labor force, in the sense that they join the inactive pool when they lose a job. Thirdly, unemployment income has little effects on employment, since it attracts people into the labor force and rises the share of attached workers. Finally, our theory suggests that contrary to two-state models, taxation of market activity increases non-participation, unattachment and adversely affects unemployment.
Keywords: J2; J30; 330; Unemployment; matching; home production; Theorie der Arbeitslosigkeit; Arbeitsuche; Anspruchslohn; Haushaltsproduktion; Arbeitsangebot; Arbeitsnachfrage; Matching; Lohn; Steuerwirkung; Beschäftigungseffekt; Theorie; USA